An Attempt to Optimize ZnO-Like TCO Nanolayered Compound Thickness in Terms of a BPES-Related Physical Parameters Pondering. (6th September 2012) - Boukhachem, A.; Amlouk, A.; Boubaker, K.; Bouhafs, M.; Amlouk, M.
Abstract : Recently, metal oxide nanolayered semiconductors revealed their increasing usefulness as UV detectors and transparent conductors in optoelectronic devices. In the present paper, a simple fabrication process has been carried out to prepare layered TCO compounds with different controlled thicknesses. Conjoint physical investigations allowed discussion of the validity of optimality in terms of geometrical parameters. A synthetic function based on pondered physical parameters was a practical guide to reach optimality.